2018
DOI: 10.1080/21645515.2018.1461298
|View full text |Cite
|
Sign up to set email alerts
|

Cationic pullulan nanogel as a safe and effective nasal vaccine delivery system for respiratory infectious diseases

Abstract: The mucosal surfaces of the respiratory and gastrointestinal tracts are continuously exposed to countless beneficial and pathologic antigens. These mucosal surfaces are thus equipped with an immune system that is unique from those elsewhere in the body; this unique system provides the first line of immune surveillance and defense against pathogen invasion. The sophisticated immune induction machinery in the aero–digestive tract involves mucosa-associated lymphoid tissues, including nasopharyngeal- and gut-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Fig 2.
Figure 1 Application of cCHP nanogel as nasal immune delivery system via nasal route [61] . cCHP is composed of a cholesteryl group-bearing pullulan (CHP) with a cationic amino group.
…”
Section: Introductionmentioning
confidence: 99%
“…Fig 2.
Figure 1 Application of cCHP nanogel as nasal immune delivery system via nasal route [61] . cCHP is composed of a cholesteryl group-bearing pullulan (CHP) with a cationic amino group.
…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the described nanocarrier is safe, and research shows that the antigens it carries do not remain in the olfactory bulb and do not accumulate in the brain, excluding the risk of neurotoxicity. All of the above information suggests that CHP is a good candidate for intranasal vaccine preparation that should be assessed in further clinical trials [56][57][58].…”
Section: Nanogelsmentioning
confidence: 99%
“…Other non-toxic nanogel systems have been synthesized using biocompatible natural polymers such as alginate, dextran, pullulan and hyaluronic acid. Studies have shown that the cells exposed to these nanogels have a high survival rate, which is evidence of low toxicity [77][78][79][80].…”
Section: Toxicity Of the Nanogelsmentioning
confidence: 99%